2019
DOI: 10.2147/opto.s191835
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of astigmatic patients with toric nesofilcon A contact lenses

Abstract: PurposeThe purpose of this evaluation was to compare the experience of habitual contact lens wearers with that of nonwearers when fitted with a novel toric nesofilcon A contact lens (Biotrue ONEday for Astigmatism lens; Bausch & Lomb Incorporated, Rochester, NY, USA), for wearer comfort, vision, and satisfaction in a real-world setting.Materials and methodsParticipating eye care practitioners (ECPs) prescribed toric nesofilcon A lenses to their astigmatic patients as part of their routine clinical practices. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…As many as 96% of patients indicated that their overall opinion of Nesofilcon A toric lenses was good or excellent. The lenses were also found to perform well in all aspects of vision and comfort tested (P < 0.001) [13].…”
Section: Discussionmentioning
confidence: 89%
“…As many as 96% of patients indicated that their overall opinion of Nesofilcon A toric lenses was good or excellent. The lenses were also found to perform well in all aspects of vision and comfort tested (P < 0.001) [13].…”
Section: Discussionmentioning
confidence: 89%